ANALISIS KORELASI LUAS LAHAN DAN PENGGUNAAN BENIH TERHADAP CAPAIAN PRODUKSI JAGUNG DI KECAMATAN DOLO KABUPATEN SIGI - Tussadia, Halimah; Pakanyamong, Ambo Abd. Kadir; Hartina (Fakultas Pertanian Universitas Tompotika Luwuk, 2025)
Corn production is one of the strategic commodities in the agricultural sector that plays an important role in supporting food security and increasing farmers’ income. The level of corn production is influenced by various production factors, including land area and seed usage. This study aims to analyze the relationship between corn production, land area, and seed usage in Dolo District, Sigi Regency. The research was conducted in 2025 involving 80 corn farmers selected purposively as respondents. The data used consisted of primary and secondary data collected through surveys, field observations, and structured interviews using questionnaires. The analytical method applied was Pearson correlation analysis to determine the strength and direction of the relationship among variables, which were further interpreted based on their level of statistical significance. The results indicate that land area has a positive and significant relationship with corn production, meaning that the larger the cultivated land, the higher the production obtained. Likewise, the appropriate use of seeds in accordance with technical recommendations and land requirements also shows a positive and significant relationship with increased production. These findings suggest that optimizing land utilization and using proper, high-quality seeds have strong potential to enhance corn productivity and overall production sustainably in Dolo District Sigi Regency.